Performance analysis of deep learning algorithms for Intrusion Detection System(IDS) of IoT Security - Fiha, Yeamin Jahan; Farjana, Mithila; Bin Masum, Syed Rifat; Soron, Mehedi Bin Sarwar; Alif, Mia Fahim Hasan (Brac University, 2022)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2022.